The Development of Integrated Piano Teaching Strategies to Enhance Music Skills for Higher Education Level - Liu, Xun; Phokha , Pramote (Journal of Roi Kaensarn Academi, 2024)
This research aims to develop and evaluate integrated piano teaching strategies designed to enhance the musical skills of higher education students. The study focused on analyzing the limitations of traditional, applied, and international piano teaching methods and integrating their strengths to create a comprehensive teaching approach. The research sample consisted of 67 piano students from Xinghai Conservatory of Music, selected through simple random sampling. The research instruments included interviews with faculty members, teaching observations, and experimental testing of the newly developed teaching strategy. Data collection involved gathering feedback from teachers and students, pre- and post-course testing, and satisfaction surveys. Data analysis was conducted to assess the effectiveness of the integrated teaching strategy in improving students' technical skills, musical expression, and overall performance. The research results found that the integrated piano teaching strategy significantly improved students' performance across various evaluation categories, including playing skills, reading and rhythm, and musical expression. The findings suggest that this comprehensive approach is effective in meeting the demands of modern piano education, offering a promising alternative to existing methods